Abdomen and pelvis computed tomography procedure: Effective dose assessment and establishment of a local diagnostic reference level - Almujally, Abdullah; Alenezi, Saad; Aldosary, Khalid Nasser; Otayni, Ahmed; Sulieman, Abdelmoneim; Abdelghani, Amr; Tamam, Nissren; Mohtasib, Rafat; Masawi, Ahmed; Moftah, Belal; Bradley, D.A. * (Elsevier, 2023)
Exposure to ionizing radiation may induce cancer risk to the patients proportional to the radiation absorbed dose and the organ sensitivity. Therefore protection of radiation exposure is essential to minimize the radiation cancer risk and prevent the deterministic effects. The International Atomic Energy Agency (IAEA) encourages member countries to establish national diagnostic reference levels (DRLs) to reduce unjustified radiation exposure. This study establishes a local DRL for computed tomography (CT) abdomen and pelvis procedures. In total, 1444 CT abdomen procedures were carried out during nine months. CT abdomen procedures were carried out at King Faisal Specialist Hospital and research center using six CT machines from different vendors. The mean and range of patients’ weight (kg) are 50 (42–120). The recommended DRLs values in DLP (mGy.cm) and CTDIvol (mGy)were 900 and 15 per CT abdomen and pelvis procedure, respectively. 3% (41 cases) were higher than the national DRL for CT abdomen and pelvis. The proposed DRL values are slightly higher than the European and the American College of Radiologists (ACR) DRL values in DLP. The purpose of DRL in terms of CTDIvol (mGy) is comparable with the international guidelines. Thus reducing the scan length, is recommended ensuring that patients receive a minimal possible radiation dose while maintaining the image quality.